(RETRACTED) Taboo of Madura Women: Patriarchal Construction in Madurese Tradition - Dahniar Th. Musa; Rupita Rupita; Nikodemus Niko (Sawwa: Jurnal Studi Gender)
Reason for Retraction (February 18th, 2022):